The Effectiveness of Acceptance and Commitment Therapy on Stress and Depression in Adolescents Aged 14 to 18 Years with Stuttering: A Randomized Controlled Clinical Trial - Zahra Babaie; Mohsen Saeidmanesh (Vesnu Publications, 2020)
Introduction: Stuttering is a communication disorder in the smooth and continuous flow of speech that occurs at different intensities. These disorders can have a negative impact on one's mental health. The purpose in this study is to determine the effectiveness of group therapy based on Acceptance and Commitment Therapy (ACT) on stress and depression in adolescents with stuttering aged 14 to 18 years. Materials and Methods: The study was performed in a randomized controlled clinical trial design and the subjects were randomly divided into the two experimental and control groups after the pre-test. The intervention was performed in 8 sessions. In the two groups, stress and depression were measured by the Depression, and Anxiety and Stress Questionnaire (DASS-21) before and after the intervention. ANCOVA was used to analyze the data. Results: The results showed that ACT significantly affected stress (P = 0.011) and depression (P = 0.014). Conclusion: The results of this study showed that ACT treatment is effective in reducing stress and depression.